κ-CASEIN GENE POLYMORPHISMS IN RIVERINE AND SWAMP BUFFALO IN INDONESIA - Rini, A.O.; Sumantri, C.; Damayanthi, E. (Diponegoro University, 2014)
Kappa-casein (κ-casein) gene is known as a gene that plays a role in controlling milk protein andalso play a crucial role in the coagulation and curdling of milk. This study was aimed to identifypolymorphisms of the κ-Casein gene of local buffaloes in Indonesia. A total number of 40 heads ofriverine buffalo and 250 heads of swamp buffalo. This study used PCR-RFLP method, whichamplification of the κ-Casein gene resulted an amplicon with length of 157 bp, located in exon 4. Theamplified fragment were digested with EcoRV restriction enzyme, which cut the κ-Casein gene in exon4 at nucleotides of GAT|ATC, revealed the presence of one polymorphism at the base position of 23 bpthat occurs with a substitution of Ile (ATC) of the T genetic variant into Thr (ACC) of the C geneticvariant. Genotyping κ-Casein gene in riverine buffalo produced two types of allele, namely C allele (157bp) and T allele (136 and 21 bp). These two alleles resulted in three types of genotypes, namely CC, CT,and TT. Frequency of the C allele was dominant to T allele. κ-Casein gene in swamp buffalo wasmonomorphic with one allele, namely C allele. Heterozygosity value of riverine and swamp buffaloeswere low. PIC value in riverine and swamp buffalo ranged 0.000-0.288. Fixation index of κ-Casein genein riverine buffalo was low (Siborong-borong SBBC = -0,0036; Deli Serdang = -0.025), but in swampbuffalo was in fixation. This study showed that κ-Casein|EcoRV were polymorphic in riverine buffaloand monomorphic in swamp buffalo.